2021
DOI: 10.1002/jclp.23129
|View full text |Cite
|
Sign up to set email alerts
|

Comparing impulsivity in borderline personality, schizophrenia and obsessional‐compulsive disorders: Who is ahead?

Abstract: Objective: Impulsivity impacts life domains and in a psychiatric context is often associated with disorders severity and stigmatization. Borderline personality disorder's (BPD), Schizophrenic disorder's (SZD), and obsessional compulsive disorder's (OCD) impulsivity issues relate to worse prognosis.This study aims to compare these disorders assessing their proneness to impulsivity and urgency.Methods: We recruited 90 patients among them OCD (n = 25), SZD (n = 23), and BPD (n = 50), and 24 healthy control partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“… Note : < or > = cohen’s d higher than .25; < or > = cohen’s d lower then. 25, Non clinical sample: n = 201, Clinical sample: n = 68, AQ12 scores extracted from Vitoratou et al [ 50 ], Hopelessness scale scores extracted from Szabó et al [ 51 ], UPPS scores extracted from Martin et al [ 52 ]; Hads scores extracted from Crawford et al [ 53 ] and Spinhoven et al [ 54 ]; Sbqr scores extracted from Osman et al [ 42 ] and Au et al [ 55 ]; + : above pathological sthresolds …”
Section: Resultsmentioning
confidence: 99%
“… Note : < or > = cohen’s d higher than .25; < or > = cohen’s d lower then. 25, Non clinical sample: n = 201, Clinical sample: n = 68, AQ12 scores extracted from Vitoratou et al [ 50 ], Hopelessness scale scores extracted from Szabó et al [ 51 ], UPPS scores extracted from Martin et al [ 52 ]; Hads scores extracted from Crawford et al [ 53 ] and Spinhoven et al [ 54 ]; Sbqr scores extracted from Osman et al [ 42 ] and Au et al [ 55 ]; + : above pathological sthresolds …”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the literature as impulsivity is one of the core symptoms of BPD. 18,[22][23][24] This result may suggest that people with high trait impulsivity are more likely to have increased symptom severity. It is interesting to note that a previous study examined the factor structure of BPD symptoms and found a 'high severity' subtype, which was associated with high impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity is regarded as a key hallmark of BPD 22,23 and is implicated across a range of disorders such as ADHD and obsessive-compulsive disorder (OCD) but may be particularly pertinent to BPD given the nature of the symptoms and prior work suggesting correlations with symptom severity in BPD. 18,[24][25][26] Impulsivity in BPD has been linked to cognitive impairments, including set-shifting deficits, which refer to the ability to switch between tasks or mental sets. Impairment in set-shifting is considered another hallmark of BPD and has been associated with increased impulsiveness, emotional dysregulation, and difficulties in forming and maintaining stable relationships.…”
Section: Introductionmentioning
confidence: 99%